Catalase activity is necessary for heat-shock recovery in Aspergillus nidulans germlings - Noventa-Jordao, M.A; Couto, R.M; Goldman, M.H.S; Aguirre, J; Iyer, S; Caplan, A; Terenzi, H.F; Goldman, G.H (Microbiology (Society for General Microbiology), 1999)
To understand the molecular mechanisms induced by stress that contribute to the development of tolerance in eukaryotic cells, the filamentous fungus Aspergillus nidulans has been chosen as a model system. Here, the response of A. nidulans germlings to heat shock is reported. The heat treatment dramatically increased the concentration of trehalose and induced the accumulation of mannitol and mRNA from the catalase gene catA. Both mannitol and catalase function to protect cells from different reactive oxygen species. Treatment with hydrogen peroxide increased A. nidulans germling viability after heat shock whilst mutants deficient in catalase were more sensitive to a 50 degrees C heat exposure. It is concluded that the defence against the lethal effects of heat exposure can be correlated with the activity of the defence system against oxidative stress.